Plasma d-asparagine and the d/l-serine ratio reflect chronic kidney diseases in children regardless of physique - Toshimasa Morishita; Naoto Nishizaki; Sakiko Taniguchi; Shinsuke Sakai; Tomonori Kimura; Masashi Mita; Mayu Nakagawa; Amane Endo; Yoshiyuki Ohtomo; Masato Yasui; Toshiaki Shimizu; Jumpei Sasabe (Amino Acids)
Abstract Biomarkers that accurately reflect renal function are essential in management of chronic kidney diseases (CKD). However, in children, age/physique and medication often alter established renal biomarkers. We studied whether amino acid enantiomers in body fluids correlate with renal function and whether they are influenced by physique or steroid medication during development. We conducted a prospective study of children 2 to 18 years old with and without CKD. We analyzed associations of serine/asparagine enantiomers in body fluids with major biochemical parameters as well as physique. To study consequences of kidney dysfunction and steroids on serine/asparagine enantiomers, we generated juvenile mice with uninephrectomy, ischemic reperfusion injury, or dexamethasone treatment. We obtained samples from 27 children, of which 12 had CKD due to congenital (n = 7) and perinatal (n = 5) causes. Plasma d-asparagine and the d/l-serine ratio had robust, positive linear associations with serum creatinine and cystatin C, and detected CKD with high sensitivity and specificity, uninfluenced by body size or biochemical parameters. In the animal study, kidney dysfunction increased plasma d-asparagine and the d/l-serine ratio, but dexamethasone treatment did not. Thus, plasma d-asparagine and the d/l-serine ratio can be useful markers for renal function in children.